Community Empowerment Through Digital Literacy in Marketing Processed Pomelo Oranges in Attangsalo Village, Ma'rang District, Pangkep Regency - Marhawati, Marhawati; Nurjannah, Nurjannah; Hidayat, Wahyu; Astuti, Sry; Nuraeni, Nuraeni (Indonesian Journal of Community Services Cel, 2023)
As a pomelo agricultural center, the Attangsalo Village faces challenges in marketing processed oranges that have not reached their optimal potential. Therefore, it is essential to empower the community through digital literacy training for marketing processed pomelo oranges in Attangsalo Village, Ma'rang District, Pangkep Regency. The goal of this program is to promote the marketing of processed pomelo oranges within the pomelo citrus farming businesses. This initiative involved approximately 30 participants, representing groups of housewives, and was carried out through participatory surveys, observations, lectures, discussions, and hands-on practice. The results of the program implementation demonstrate the participants' dedication and enthusiasm during each training session. Several technical aspects, including the utilization of social media for marketing processed pomelo oranges, were comprehensively understood by the program partners. Furthermore, participants were able to apply the training during the practical learning sessions.